Polyimide surface modification by linear stationary plasma thruster - Choi, Won-Kook; Park, Dong-Hee (ELSEVIER SCIENCE SA, 2009)
Compared to the conventional circular type, the horse-track shaped proto-type linear stationary plasma thruster (LSPT) was designed and fabricated. A cathode with LaB6 emitter was adopted for trapped electron motion along ceramic wall as an electron source generally attached in the conventional cylindrical SPT. Nevertheless it has a little lower ion beam current density of 0.5 mA/cm(2) than conventional cylindrical type SPT with 50 mm diameter, it was also proved very effective in surface modification of polymers. Reactive O-2(+) and N2O+ ion beam generated from LSPT can reduce the wetting angle 70 degrees of polyimide (PI) down to the small angle less than 10 degrees. 2-layer non-adhesive flexible copper clad laminate (FCCL) with Cu(8 mu m)/Cu(200 nm)/Ni-Cr-Mo (20 nm)/PI(38 mu m) was fabricated by using LSPT in 300 mm roll-to-roll vacuum coater. Peel strength was 0.66 kgf/cm for as-received sample and 0.42 kgf/cm after thermal test for 168 h at 150 degrees C, which shows a little higher performance than commercial ones. (C) 2009 Elsevier B.V. All rights reserved.